Trash detection in an aquatic environment - Roshni, Nishat Mahmud; Arefin, Meshkatul; Joy, Kazi Masfiqul Alam; Hassan, Marjanul; Karmakar, Shashwata (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.